Simple Application of Time Correlated Single Photon Counter of Picosecond Pulsed Laser to Measure Refractive Index of Saline Solution - Isnaeni, Isnaeni; Mulyawan, Reynaldi Gilang; Hakimi, Ahmad Reza (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2019)
Time correlated single photon counter was design for measuring fluorescence lifetime of emitting materials. It was designed for photonics basic research and science that is usually done in a laboratory. Furthermore, time correlated single photon counter can be used to measure simple and more practical optical properties of materials, such as refractive index. However, since the system was not designed for this practical application, a simple setup modification and calculation is required. In this work, time correlated single photon counter is utilized to measure the refractive index of sodium chloride solutions. The measurement was done using simple time of flight calculation of each pulse of picosecond pulsed laser. Our measurement was done on different concentrations of sodium chloride that have different refractive indices. It was found that the measurement technique and calculation was able to produce consistent quantitative calculation of refractive indices. Â